Non-linear response of a moored LNG ship subjected to regular waves. (18th August 2021) - Rudan, Smiljko; Karačić, Josip; Ćatipović, Ivan
ABSTRACT: The present work considers application of the state-of-the-art numerical tools, such as LS-Dyna, in analysis of the floating storage regasification unit (FRSU) response affected by the waves, but also by the mooring lines and fenders, forming together a highly non-linear problem. A time-domain simulation methodology for solving the problem described is presented. Firstly, hydrodynamic properties of a rigid floating vessel are determined, that is ship hydrostatic, damping and added mass properties. Linear hydrodynamic theory based on the potential flow model is applied to find solution in frequency domain. Then, mapping hydrodynamic properties from the frequency to the time domain is conducted by LS-Dyna MCOL module. Secondly, a model is made in LS-Dyna considering realistic non-linear properties of mooring lines and fenders to get coupled response of FSRU due to waves and mooring system. Forces in mooring system, ensuring safe FSRU station keeping, are then determined, and obtained results discussed.